Application of Zeolite as Carrier for Humic Acid for Increasing Food Crops Production - Suwardi Suwardi; Evi Mutiara Dewi; Bagus Ahmad Hermawan (Institut Teknologi Bandung, 2009)
Soils in Indonesia are mostly classified as Ultisol having physico-chemical properties such as low pH, low organic matter and very low in nutrients. As a result, the agricultural production on land is very low. Today the use of chemical fertilizers without addition of organic matter to cause a decline in soil organic matter content, soil physical properties become increasingly hard due to structural damage and no development of most soil microorganisms. In such conditions, the soil becomes no more responsive to fertilization so that agricultural production including food crops is leveling of. Therefore, efforts to overcome the barriers of soil properties to increase production of food crops must be done. Recently busy talking people active ingredients that can increase agricultural production spectacular. The material is humic acid extracted from organic materials. The result of this study showed that application of 10 liter/ha humic acid to the soils through zeolite as carrier increased the production of paddy by 15% and corn by 10%. The increase of crop production is due to the development of root then stimulating the absorption of nutrients